Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/aepp.13328
|View full text |Cite
|
Sign up to set email alerts
|

Usual nutrient intake and dietary quality of low‐income U.S. older adults

Abstract: We estimate nutrient intake from diet and total sources including dietary supplements (DS), and dietary quality of low‐income U.S. older adults (60+ years) using the 2007–2016 National Health and Nutrition Examination Survey. We apply the National Cancer Institute method to determine usual/habitual nutrient intake distributions. Our results reveal that low‐income older adults have poor nutrient intake and dietary quality. DS use reduces the risk of nutrient inadequacy but is not associated with statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This key result is consistent with the quantitative work of Brucker et al (2020). Qin et al (2023) examine the use of dietary supplements among low-income seniors. To do so, they used data from the 2007-2016 National Health and Nutrition Examination Survey (NHANES) with a sample composed of households with incomes less than 130% of the poverty line.…”
Section: Risk Factors For Food Insecurity Among Senior Householdsmentioning
confidence: 99%
“…This key result is consistent with the quantitative work of Brucker et al (2020). Qin et al (2023) examine the use of dietary supplements among low-income seniors. To do so, they used data from the 2007-2016 National Health and Nutrition Examination Survey (NHANES) with a sample composed of households with incomes less than 130% of the poverty line.…”
Section: Risk Factors For Food Insecurity Among Senior Householdsmentioning
confidence: 99%
“…This decline may signal challenges in accessing healthier food options, which are linked to limited physical access to nutritious food. This situation is even more dire when considering low-income older adults, as highlighted in the study by Qin et al, 2022, where poor nutrient intake and dietary quality were observed in low-income older adults older than sixty in the United States [ 22 ]. Similarly, Selvamani and Elgar in 2022 found that among middle-aged and older persons in India, food insecurity emerged as a significant social determinant associated with several measures of poor health and wellbeing [ 23 ].…”
Section: Defining Food Security and Mental Healthmentioning
confidence: 99%
“…Existing studies have shown that income is one of the main factors influencing dietary quality (66,(68)(69)(70). Low-income older adults have poor nutrient intake and dietary quality (71). Therefore, work and improved income will undoubtedly make people underline the nutrition of food and their own health, which contributes to better dietary quality.…”
Section: Comparison To the Existing Literaturementioning
confidence: 99%